Applying Intergroup Relations Research to Understanding LGB Health Disparities. (21st September 2017) - Ryan, William S.; Hunger, Jeffrey M.; Major, Brenda
Abstract: This article describes how intergroup processes and stigma contribute to pervasive health disparities that exist between LGB and heterosexual individuals. In particular, we focus on how the hierarchical organization of groups and the intergroup dynamics that arise from this structure operate at structural, interpersonal, and intrapersonal levels to impact psychological and physiological processes that negatively influence health among LGB individuals. We focus on how these various manifestations of stigma act as additional stressors with which LGB individuals must contend and how this stress impacts health via stress‐related physiological reactivity, coping strategies, and health care interactions. Throughout we highlight how specific aspects of LGB identities (i.e., concealability and "nontribal" nature) present concerns that diverge from those documented in research on race and gender‐based stigmas. We end by discussing areas for future research and implications for social policy and interventions.